Comparison of foot-stretcher force profiles between onwater and ergometer rowing - Baca, A.; Kornfeind, P.; Heller, M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to compare the reaction forces at the foot stretcher of a Concept2 ergometer with and without slides to those of the boat in single scull rowing. Four male elite rowers were tested at rates of 20 and 30 strokes per minute on the ergometer with and without slides as well as in a single scull. The coefficient of multiple determination showed a high consistency about five time-normalised successive strokes in all conditions (about 0.99). Cross-correlation calculations between on-water force curves and force curves obtained under both ergometer conditions showed higher similarities for the ergometer on slides.